Toxicological effects of ciprofloxacin and chlorhexidine on growth and chlorophyll a synthesis of freshwater cyanobacteria - Azevedo, Fernanda Cristina Rezende (2019)
Cyanobacteria are phytoplanktonic microorganisms that are susceptible to the deleterious effects of pharmaceutical residues in the aquatic environment, which poses a challenge to the environment exposed to diverse pharmaceutical products and their potential effects. The objective of this study was to evaluate the effects of the antibiotic substances ciprofloxacin and chlorhexidine in pharmaceutical preparations on the growth and production of chlorophyll of two cyanobacterial strains, Microcystis aeruginosa and Microcystis panniformis, isolated from a lake in a Brazilian environmental protection area. The EC50 and EC10 of chlorhexidine for M. aeruginosa were 206.4 μg/L and 108.5 μg/L, respectively, and for M. panniformis were 171.4 μg/L and 116.6 μg/L, respectively. The EC50 and EC10 of ciprofloxacin for M. aeruginosa were 17.24 μg/L and 3.21 μg/L, respectively, and for M. panniformis were 13.56 μg/L and 1.50 μg/L, respectively. The toxicity of the antibiotic ciprofloxacin (drug) and chlorhexidine (standard solution) to the Microcystis species was demonstrated, and these species were both very sensitive to ciprofloxacin. Our results suggest that the strains of M. aeruginosa and M. panniformis may be affected by exposure to residues of ciprofloxacin (>1.5 μg/L), which may represent a risk to the survival of aquatic species.